Innovations in insuring the poor: Risk, poverty and insurance - Dercon, Stefan (International Food Policy Research Institute, 2009)
Risk is pervasive in developing countries. The standard household risks of sickness, mortality, fire, theft, and unemployment are especially severe for poor families in developing countries. Rural households, most of which derive their livelihoods from the land, face the additional risks of droughts, floods, and pests and diseases affecting their crops and livestock. Insurance provision is still limited, and state-provided social security or more basic social safety nets are often limited or unavailable for particular widespread disasters. Richer families have reasonable access to insurance alternatives, such as credit and substantial savings. Although these alternatives are generally not options for poorer families, it is well known that such families do employ relatively sophisticated mechanisms to manage and cope with risk. They tend to diversify their crops and income-generating activities, often incorporating nonfarm activities into their income streams and even having family members migrate to reduce the household’s overall exposure to risk. Where possible, they build up savings for precautionary purposes, often in the form of livestock or other liquid assets. They also engage in informal mutual support networks in which assistance is provided if a member experiences some form of shock. Nevertheless, given the variety and severity of risks to be dealt with, shocks inevitably have serious welfare consequences. These consequences are well illustrated by evidence from Ethiopia, where rural households face a considerable risk of drought. For example, about half of the households interviewed in 2004 for a rural panel data survey in 15 communities across the country reported that they faced serious hardship due to drought in the preceding five years, while about a quarter of the sample reported hardship resulting from illness and a similar number reported problems related to illness. Despite increased investment in health services and a relatively widespread, foreign aid–supported safety net to cope with drought, these shocks continue to impose significant welfare costs. The consumption levels of those reporting a serious drought, for example, were found to be 16 percent lower than those of families not affected, and shocks from illness appeared to have similar average impacts. Further, the costs were not just short term: in the sample, it was found that those who had suffered considerably in the 1984–85 famine—the most severe famine in recent history—were still experiencing lower growth rates in consumption in the 1990s, a period of overall recovery, than those who were not seriously affected by the famine. Children born during the famine were found to be up to three centimeters shorter at adulthood than children born before or after the famine, suggesting that famine had serious, persistent health impacts with long-term consequences. Risk should thus be seen as a cause of persistent poverty, in that shocks cause serious losses of physical assets and human capital. The presence of risk also tends to induce poorer households to become risk averse, even at the expense of otherwise higher returns: for example, they may choose to grow low-returning but safe crops and to avoid committing resources to more productive capital in order to preserve the liquidity of their asset base. In Ethiopia, efforts to increase farmers’ fertilizer use and thereby raise their productivity—a risky undertaking as farmers must still bear the costs of fertilizer even if the harvest fails—are significantly undermined by the lack of protection against poor rainfall. Evidence from other countries shows similar patterns: risk induces farmers to engage in low-return investment portfolios in rural India and to grow more low-risk, low-return crops such as sweetpotatoes or cassava in Tanzania. Climate and other shocks have been shown to undermine long-term nutrition, educational achievement, and earnings in settings as diverse as India, Indonesia, Tanzania, and Zimbabwe. These studies all show that risk causes poverty to persist.